Isu-Isu Politik dalam Kampanye Calon Presiden RI terhadap Preferensi Pemilih di Nusa Tenggara Barat - Khaldun, Ibnu (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Provinsi Sumatera Utara, 2024)
This study examines the preferences of voters in West Nusa Tenggara (NTB) in the context of the 2024 Indonesian presidential election and how various political issues influence their choices. Utilizing a quantitative approach and descriptive survey, data was collected from 2,672 respondents representing diverse educational and occupational backgrounds in the NTB region. The findings reveal various political issues affecting voter preferences, including economic, social, environmental, security, leadership, and other issues. The most dominant issue in NTB voters' preferences is Nationalist Religious Issues, with about 24% of respondents considering it the most important issue. Socialism and Cultural Issues also receive significant attention, reflecting concern for the preservation of local culture and social integration. Additionally, Education and Public Health Issues are high priorities for NTB voters, indicating the need for access to quality education and good healthcare services. This research provides a deeper understanding of the political dynamics in NTB and the factors influencing voter decisions. The results can guide presidential candidates and political parties in designing campaign platforms relevant to the needs of this region. Furthermore, this study can help enhance political participation, advance important issues, and strengthen political representation at the local level. Recommendations are given for further studies on the role of religion in NTB politics, evaluation of issue fulfillment in public policy, analysis of demographic changes, and studies on political participation in NTB. This research is expected to provide valuable contributions to understanding regional politics in Indonesia and voter preferences that could influence the outcome of the 2024 presidential election in NTB.